Magnetization switching in high-density magnetic nanodots by a fine-tune sputtering process on a large-area diblock copolymer mask. Issue 43 (27th October 2017) - Barrera, G.; Celegato, F.; Coïsson, M.; Manzin, A.; Ferrarese Lupi, F.; Seguini, G.; Boarino, L.; Aprile, G.; Perego, M.; Tiberto, P.
Abstract : Magnetic properties and micromagnetic simulations of large-area arrays of Co nanodots obtained by a fine-tuned sputtering process on a diblock-copolymer mask. Abstract : Ordered magnetic nanodot arrays with extremely high density provide unique properties to the growing field of nanotechnology. To overcome the size limitations of conventional lithography, a fine-tuned sputtering deposition process on mesoporous polymeric template fabricated by diblock copolymer self-assembly is herein proposed to fabricate uniform and densely spaced nanometer-scale magnetic dot arrays. This process was successfully exploited to pattern, over a large area, sputtered Ni80 Fe20 and Co thin films with thicknesses of 10 and 13 nm, respectively. Carefully tuned sputter-etching at a suitable glancing angle was performed to selectively remove the magnetic material deposited on top of the polymeric template, producing nanodot arrays (dot diameter about 17 nm). A detailed study of magnetization reversal at room temperature as a function of sputter-etching time, together with morphology investigations, was performed to confirm the synthesis of long-range ordered arrays displaying functional magnetic properties. Magnetic hysteresis loops of the obtained nanodot arrays were measured at different temperatures and interpreted via micromagnetic simulations to explore the role of dipole–dipole magnetostatic interactions between dots and the effect of magnetocrystalline anisotropy. The agreement between measurements and numerical modelling results indicates the use of the proposed synthesis technique as an innovative process in the design of large-area nanoscale arrays of functional magnetic elements.